Albinism in Hura polyandra Baill. (Euphorbiaceae): morphological and histological aspects - Delgado-Paredes, Guillermo; Rojas-Idrogo, Consuelo; Bazán-Sernaqué, Pilar; Vásquez-Díaz, Cecilia; Esquerre-Ibañez, Boris; Zuñe Da-Silva, Felipe; Kuethe, J.R. (Revista de Biologia Neotropical / Journal of Neotropical Biology, 2024)
Albinism in plants is the inability to produce chlorophylls, limiting the photosynthesis process, which causes abnormal plant development and premature death. Albinism is an unusual phenomenon in plants found in their natural environments, however, it is a frequent phenomenon in the production of haploids by anther culture and somatic hybrids through protoplast fusion. The objective of this study was to determine some morphological characteristics of fruits and seeds and to establish the relationship with the occurrence of albino seedlings, as well as some histological characteristics in this type of seedlings, obtained from a mother plant of ‘habilla’ Hura polyandra, comparing it with normal green seedlings. The parental plant was collected in Salas (Lambayeque, Peru), from an isolated population without other individuals present in the surrounding 10 km. The theory of what was postulated for tropical trees, in that albinism in H. polyandra is predominantly caused by self-pollination and genetic inbreeding.